REMOVAL OF ASH AND SULFUR FROM COAL OF EAST KALIMANTAN BY BIOOXIDATION AND BIOFLOTATION METHODS - Arifin, Mubdiana
Coal is one of the alternative fuels, which potentially provides most of the domestic energy needs. The steam-powered electric generator (PLTU) is a sector that dominates the utilization of domestic coal. Sulfur contained in the coal is an impurity element apart from other contaminants such as ash, soil, rocks, and minerals. The combustion of high-sulfur coal produces SO2, which can interfere the human health, such as causing tightness in the respiratory tract, as well as the environment by causing acid rain and corrosion on plant equipment. Various efforts have been made by reducing the levels of sulfur to minimize the negative impact caused by coal combustion. Biodesulfurization using bacteria has been developed and widely studied as an alternative treatment to remove the sulfur and ash from the coal. Therefore, the purpose of this study was to remove the sulfur and ash from coal using various types of mixotrophic bacteria by the biooxidation and bioflotation methods. The current study used coal from East Kalimantan of Indonesia with a total sulfur and ash content of 2.56 and 7.21%, respectively. A series of biotreatment experiments were carried out, such as biooxidation optimization variables that included particle size, bacterial type, and biooxidation process time and bioflotation process variables, including variations in slurry pH, bacterial inoculum and time of bacterial adaptation to coal. Biooxidation experiments were carried out in duplicate in Erlenmeyer flasks placed on a rotary shaker at 180 rpm at room temperature. Besides, the bioflotation tests were carried out using the Denver flotation cells with a capacity of 1,375 mL and an impeller rotational speed of 1,150 rpm. Experimental analyses were conducted, including proximate analysis, total sulfur, and caloric value following standard methods (ASTM D3173 for moisture content, ASTM D3174 for ash content, and ASTM D3175 for the volatile matter). To determine the quality of coal before and after biomining treatment, sulfur contents in coals were measured according to ASTM D3177 (for total sulfur). On the other hand, the calorific value of the initial coal used in this study was also measured based on ASTM D2015. Mineral contents in coal samples were analyzed using XRD (X-Ray Diffraction), and FTIR analysis (Fourier Transform InfraRed) was also performed to determine the functional groups or chemical bonds in coal before and after biooxidation and bioflotation processes. The results of the biooxidation experiment showed that the bacteria Alicyclobacillus ferrooxydans, Micrococcus luteus, and a mixed culture of Alicyclobacillus ferrooxydans and Micrococcus luteus were capable of removing sulfur from coal with percent removal of 59.42%-db, 37.95%-db and 24.29%-db, respectively. In addition, ash removal was also increased to reach percent removal of 41.35%-db (for A. ferrooxydans), 66.56%-db (for M. luteus) and 27.07%-db (for mixed culture). Both bacteria and mixed culture were able to eliminate sulfur and ash under biooxidation conditions of 20% (v/v) bacterial inoculum, a particle size of -35 mesh, and biooxidation time of 30 days. Moreover, the results of bioflotation experiments using A. ferrooxydans achieved sulfur and ash removal by 29.49%-db and 34.39%-db, respectively. The optimized bioflotation processes were conducted at pH 4 with 10% (v/v) bacterial inoculum and 10% w/v pulp density. Therefore, biotreatment technology using bioflotation and biooxidation methods can be an alternative to reduce the high sulfur and ash content of coal, because the technology is environmentally friendly and does not change the nature of coal.